Exploration of the regulatory mechanisms of regeneration, anti-oxidation, anti-aging and the immune response at the post-molt stage of Eriocheir sinensis - Wang, Meiyao; Ge, Jiachun; Ma, Xingkong; Su, Shengyan; Tian, Can; Li, Jianlin; Yu, Fan; Li, Hongxia; Song, Changyou; Gao, Jiancao; Xu, Pao; Tang, Yongkai; et al. (Frontiers in Physiology, 2022)
Eriocheir sinensis is widely appreciated by the surrounding population due to its culinary delicacy and rich nutrients. The E. sinensis breeding industry is very prosperous and molting is one of the important growth characteristics. Research on the regulation of molting in E. sinensis is still in the initial stages. There is currently no relevant information on the regulatory mechanisms of heart development following molting. Comparative transcriptome analysis was used to study developmental regulation mechanisms in the heart of E. sinensis at the post-molt and inter-molt stages. The results indicated that many regulatory pathways and genes involved in regeneration, anti-oxidation, anti-aging and the immune response were significantly upregulated after molting in E. sinensis. Aside from cardiac development, the differentially expressed genes (DEGs) were relevant to myocardial movement and neuronal signal transduction. DEGs were also related to the regulation of glutathione homeostasis and biological rhythms in regard to anti-oxidation and anti-aging, and to the regulation of immune cell development and the immune response. This study provides a theoretical framework for understanding the regulation of molting in E. sinensis and in other economically important crustaceans.